Vincentian Education and the Charism of St. Vincent de Paul - Dosen, CM, Anthony J. (Catholic Education: A Journal of Inquiry and Practice, 2005)
St. Vincent de Paul is a popular saint in the contemporary practice of Catholicism. This article explains why, providing a historical overview of the many influences in Vincent’s life and demonstrating how central Vincentian themes can be incarnated in educational institutions. Vincent’s passion”love of the poor”remains a compelling challenge today.